Biogas Cleaning and Pretreatment - Sirichai Koonaphapdeelert (2020)
© 2020, Springer Nature Singapore Pte Ltd. This chapter deals with the processing of raw biogas, directly from the anaerobic digester. This biogas generally contains undesirable components which are corrosive to metals and toxic to health and the environment. Before the biogas is sent to an upgrading unit, it requires some pretreatment to remove and minimize contaminants which might cause damage. Depending on the anaerobic digester, the contaminants might vary but the two main ones are hydrogen sulfide and moisture. In agricultural digesters, the H2S level can range from 1000 to 4000 ppm. Even in small local digesters, used only for generating on-site power in an old generator, the hydrogen sulfide should be kept below 200 ppm or else it seriously affects the life of the engine. For larger scale upgrading plants, especially membrane and PSA technologies, a more systematic approach should be taken to biogas pretreatment. All possible contaminants are briefly introduced and discussed but only the engineering design for H2S removal and moisture reduction is explained in detail in this chapter. Chapter 3 deals with specific upgrading technologies.